2002
DOI: 10.1038/sj.bjp.0704498
|View full text |Cite
|
Sign up to set email alerts
|

Transient relaxation of rat mesenteric microvessels by ceramides

Abstract: 1 We have investigated the vasodilating eects of D-erythro-C2-ceramide (C2-ceramide) in methoxamine-contracted rat mesenteric microvessels. 2 C2-ceramide (10 ± 100 mM) caused a concentration-dependent, slowly developing relaxation which reached maximum values after &10 min and partially abated thereafter. 3 Endothelium removal or inhibitors of guanylyl cyclase (3 mM ODQ), protein kinase A (10 mM H7, 1 mM H89) and various types of K + channels (10 mM BaCl 2 , 3 mM tetraethylammonium, 30 nM charybdotoxin, 30 nM … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 29 publications
0
21
0
Order By: Relevance
“…Nevertheless, it must be stated that even combined inhibition accounted for only two thirds of the overall response against passive tension and did not at all explain relaxation against active tension. A similar synergistic effect was recently demonstrated for vascular smooth muscle relaxation by ceramide, which was only weakly sensitive to inhibition of guanylyl cyclase or BK Ca channels, whereas their combined inhibition abolished it (Czyborra et al, 2002).…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…Nevertheless, it must be stated that even combined inhibition accounted for only two thirds of the overall response against passive tension and did not at all explain relaxation against active tension. A similar synergistic effect was recently demonstrated for vascular smooth muscle relaxation by ceramide, which was only weakly sensitive to inhibition of guanylyl cyclase or BK Ca channels, whereas their combined inhibition abolished it (Czyborra et al, 2002).…”
Section: Discussionmentioning
confidence: 66%
“…Potassium channel opening, particularly as induced by BK Ca channel openers, mediates relaxation (Malysz et al, 2004). Some previous studies have linked ␤-adrenergic receptor stimulation to potassium channel opening (Czyborra et al, 2002;Horinouchi et al, 2003;Kathöfer et al, 2003). Specifically, it has been shown that ␤-adrenergic receptor stimulation in guinea pig urinary bladder activates BK Ca channels (Kobayashi et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…9 It can be hypothesized that this rheostat also plays a role in vascular contraction and relaxation because S1P, sphingosine, and ceramide are potentially counteracting, vasoactive compounds. 10,11 The molecular basis of ceramide effects has not been explored fully but is believed to involve stress-activated protein kinases, protein phosphatases such as protein phosphatases 1 and 2, guanylyl cyclase, and charybdotoxinsensitive K ϩ channels. 11,12 The molecular basis of S1P effects has been characterized in more detail.…”
mentioning
confidence: 99%
“…10,11 The molecular basis of ceramide effects has not been explored fully but is believed to involve stress-activated protein kinases, protein phosphatases such as protein phosphatases 1 and 2, guanylyl cyclase, and charybdotoxinsensitive K ϩ channels. 11,12 The molecular basis of S1P effects has been characterized in more detail. S1P can act on specific G protein-coupled receptors, of which 5 subtypes have been identified thus far, termed S1P [1][2][3][4][5] .…”
mentioning
confidence: 99%